Peningkatan Kapasitas Bahan Pakan Ternak Bebek di UMKM Ternak Bebek Junrejo Batu Jawa Timur: Increasing Feed Capacity in the Junrejo Batu Duck Farming MSME East Java - Yepy Komaril Sofi'i; Ali Saifullah; Roro Heni Hendaryati; Sudarman Sudarman; Rusnita Yuliana; Aril Reynaldi; Muhammad Sukroni; Willy Satrio Nugroho (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Partners in this service are MSME Duck Livestock, located in Junrejo, Batu. This partner currently uses conventional methods in carrying out the process of mixing animal feed. Therefore, the purpose of this service is to introduce and implement mechanization in the animal feed mixing process through the use of animal feed mixing machines. The animal feed mixer machine used has a capacity of 10 kg. The motor power used is 0.25 Horsepower (HP). The dimensions of this machine reach 740mm x 310mm x 550mm. This machine is equipped with four straight mixers used in mixing animal feed. Through the evaluation that has been carried out, the use of this animal feed mixing machine is proven to provide significant benefits. Mixing animal feed ingredients, which previously required quite a long time, has been shortened to only 3 minutes for every 10 kg of feed ingredients. This increase in efficiency is significant for MSME Duck Animal Feed. With the animal feed mixing machine, our partners can increase productivity and efficiency in their business. In addition, this machine also helps improve the consistency and quality of mixing feed, thereby positively impacting the growth and health of the ducks they care for. Overall, using animal feed mixing machines in this service has a significant positive impact on MSMEs of Duck Animal Feed. By increasing the productivity, efficiency, and quality of mixing animal feed, it is hoped that our partners can sustainably develop their businesses and increase their income.